Existence and uniqueness results for Kirchhoff–Schrödinger–Poisson system with general singularity. Issue 16 (10th December 2017) - Li, Fuyi; Song, Zhaoxia; Zhang, Qi
Abstract: In this paper, under the general singular assumptions on f, we discuss the existence and uniqueness of solution to a class of Kirchhoff–Schrödinger–Poisson system. For the existence of solution, we assume that f is nonincreasing on and satisfies general singularity at zero, and sublinear growth at infinity. Furthermore, we also obtain the unique result assuming that f satisfies one side Lipschitz condition on . The variational method is employed to discuss the existence and uniqueness of solution to this system.